Energy correlations of prompt neutrons from 252Cf fission - Whittal, David Mark (Department of Physics, 2016)
Measurements have been made of the neutron-neutron energy correlations for coincident neutrons emitted in the spontaneous fission of ²⁵²Cf. The hypothesis that cooling of the fission fragments during the cascade evaporation of prompt neutrons affects the energies of successive neutrons in a cascade has been investigated by a comparison of the energy correlations of coincident neutrons from the same fragment with those of coincident neutrons from opposite fragments in the same fission. It is found that the energies of coincident neutrons are posftively correlated and that the correlation coefficient is greater for neutrons from opposite fragments than for neutrons from the same fragment. This provides a sensitive test of the nature of neutron emission in an evaporation cascade. The energy correlations of random (noncoincidental) neutrons have also been investigated and are found to show similar but smaller correlation trends. It is concluded that there is some evidence for the cascade cooling effect on the energies of prompt fission neutrons.